Effects of Rapamycin Combined with Low Dose Prednisone in Patients with Chronic Immune Thrombocytopenia - Jiaming Li; Zhaoyue Wang; Lan Dai; Lijuan Cao; Jian Su; Mingqing Zhu; Ziqiang Yu; Xia Bai; Changgeng Ruan (Clinical and Developmental Immunology)
We conducted this randomized trial to investigate the efficacy and safety of rapamycin treatment in adults with chronic immune thrombocytopenia (ITP). Eighty-eight patients were separated into the control (cyclosporine A plus prednisone) and experimental (rapamycin plus prednisone) groups. The CD4+CD25+CD127low regulatory T (Treg) cells level, Foxp3 mRNA expression, and the relevant cytokines levels were measured before and after treatment. The overall response (OR) was similar in both groups (experimental group versus control group: 58% versus 62%, P=0.70). However, sustained response (SR) was more pronounced in the experimental group than in the control group (68% versus 39%, P<0.05). Both groups showed similar incidence of adverse events (7% versus 11%, P=0.51). As expected, the low pretreatment baseline level of Treg cells was seen in all patients (P<0.001); however, the experimental group experienced a significant rise in Treg cell level, and there was a strong correlation between the levels of Treg cells and TGF-beta after the treatment. In addition, the upregulation maintained a stable level during the follow-up phase. Thus, rapamycin plus low dose prednisone could provide a new promising option for therapy of ITP.